Subjective symptoms are triggers for the detection of immune checkpoint inhibitor-induced interstitial lung disease and associate with disease severity: a single-center retrospective study - Mari Yokoi; Atsushi Yonezawa; Daiki Hira; Tomohiro Handa; Kiminobu Tanizawa; Shunsaku Nakagawa; Masahiro Tsuda; Yasuaki Ikemi; Ryo Itotani; Hironori Yoshida; Motoo Nomura; Junichi Matsubara; et al. (Journal of Pharmaceutical Health Care and Sciences, 2024)
Abstract Background Interstitial lung disease (ILD) is one of the most common fatal immune-related adverse events (irAEs). ILD development adversely affects the continuation of anticancer drug therapy, including immune checkpoint inhibitor (ICI) therapy and prognosis. There are no established useful clinical indicators for the early detection of ILD. Furthermore, the factors that lead the attending physician to suspect ICI-induced ILD (ICI-ILD) remain unclear. This study aimed to investigate the ICI-ILD detection based on subjective symptoms and their relationship with disease severity in patients receiving anti-PD-1/PD-L1 antibody. Methods This was a retrospective observational study. We enrolled the patients who received anti-PD-1/PD-L1 antibody at Kyoto University Hospital between September 2014 and April 2021. Patients who developed ICI-ILD were stratified into two distinct groups based on factors that triggered the suspicion of ILD development. The “Subjective symptoms” group was defined as patients in whom ILD was detected based on subjective symptoms. Conversely, the “Routine examinations” group was defined as patients in whom ILD was suspected based on scheduled routine examinations. The severity of ILD in each group was assessed and its association with changes in the respiratory symptoms was examined. Results Of 926 patients who received anti-PD-1/PD-L1 antibody, 51 patients (5.5%) developed ICI-ILD. The incidence of ICI-ILD in patients with lung cancer was significantly higher than that in patients with other cancers (P < 0.001). Among the patients with ICI-ILD, 27 patients (52.9%) were classified into the “Subjective symptoms” group. The “Subjective symptoms” group exhibited a significantly higher proportion of Grade 3–5 ICI-ILD cases than the “Routine examinations” group (76.2% vs. 23.8%, P = 0.010). At the last visit, before the suspected onset of ILD, 21 of the 27 patients (77.8%) had no symptoms or no change in the respiratory symptoms. Conclusion Subjective symptoms triggered the suspicion of Grade 3–5 ICI-ILD. Enhanced monitoring and patient education could be essential for the early detection of ICI-ILD because ILD may develop rapidly. Our findings might help to manage ICI-ILD in clinical practice.